Polycythemia: a mystery solved by history - Kalal, Chetan; Patel, Atif; Wagh, Adinath; Joshi, Harshad; Jain, Samit; Surude, Ravindra; Bhatia, Shobna; Bhatt, Chetan (International Journal of Research in Medical Sciences, 2020)
Testosterone is responsible for increased muscle mass. Leaner body mass helps control weight and increases energy. High levels of testosterone help build muscles and also stimulate growth in strength. Androgenic-anabolic steroids (AAS) are drugs that are structurally related to the cyclic steroid rings system and have similar effects to testosterone in the body. Athletes who abuse steroids do so for muscle growth and quick recovery. Testosterone - whether it's injected, applied via a patch or cream, or taken orally - allows athletes to rapidly increase muscle mass beyond their usual capacity, and also reduces their recovery time which allows them to train continuously with little need to rest their bodies in between workouts. Physiologically, erythrocytosis is defined by an erythrocyte mass that exceeds 125% of that predicted for sex and body mass. Much of the concern with the use of testosterone involves increase in blood viscosity, resulting from increased red blood cell mass causing a potential increased risk for venous thromboembolism (VTE), myocardial infarction (MI), and cerebrovascular accidents (CVA). We report a case of secondary polycythemia related to testosterone therapy.